Young children solving additive structure problems - Mamede, Ema (2012)
This paper describes a study to analyse how 4-6-year-olds (N=45) children solve different types of additive reasoning problems. Individual interviews were conducted on kindergarten children when solving the problems. Their performance as well as their explanations were analysed when solving additive reasoning problems. The additive reasoning problems comprised simple, inverse and comparative problems. Results suggested that Portuguese kindergarten children have some informal knowledge that allowed them to solve additive structure problems with understanding. Children performed better in the simple additive problems and found the comparative problems more difficult.